Development of Heart Rate and Oxygen Saturation Measurement Device using MAX30100 Sensor based on Internet of Things (IoT) for Monitoring Fitness - Aida Rahmawati (Journal of Holistic Medical Technologies (JHMT), 2025)
The heart is an organ that circulates blood throughout the body. Heart health can be measured through cardiac parameters such as BPM and blood oxygen saturation (SpO2). Public busyness has become an obstacle in monitoring health status. This condition prompted researchers to collect data, analyze it, design the device, and conduct accuracy tests on the sensors used in the designed system. This system is designed to provide health information to users by providing real-time access to data at their fingertips during exercise. The devices used include the MAX30100 sensor which detects heart rate and the NodeMCU ESP8266 module which connects the system to the cloud (IoT), as well as a smartphone that displays data accuracy results through Blynk. The displayed data is then identified.